AN ANALYSIS OF STUDENTS’ DIFFICULTIES IN SPEAKING ENGLISH AT LPK ISI PRINGSEWU - Garda Arif Wicaksono (Jurnal Penelitian Humaniora, 2022)
The purpose of this research were first,  to investigate the students’ difficulties in speaking English  second, to know the expressions while thier doing conversation. This types of this study is qualitative especially focuses on descriptive analytical method. The research used fifteen students of ISI Pringsewu as subject of this research. The data were collected thorugh some of videos and transcript of conversation. The result of this reserach showed that 25% of the students have good in grammar, 10% of the students speak English in true pronunciation, 18% of the students have good in vocabulary and 69% of the students have good in pronunciation. It can be concluded that the students have good fluency in speak English. However, most of the students’ difficulties in grammar, pronunciation, and vocabulary. This is because students feel not need grammar while speaking, less of vocabulary or lazy to adding their of vocabulary, less of practice pronunciation or lazy to search how to say each words